Utilizing Internet of Things (IoT) Technology in Recirculating Aquaculture Systems for Enhancing Water Quality and Health of Catfish (Clarias sp.) at Pokdakan Bintang Rosela Jaya, Pringsewu - Sarida, Munti; Mufita, Halimah; Hidayat, Muhammad Adil; Alfina, Ria; Sulistiono, Wahyu Eko; Setyawan, Agus; Azizah, Azizah (PT. Riset Press International, 2025)
This community service program is motivated by the necessity to enhance the productivity and efficiency of catfish farming in the Pringsewu Regency of Lampung, particularly in the face of challenges posed by water quality variability and climate change. Conventional fish farming systems frequently encounter obstacles such as temperature instability, pH fluctuations, and elevated ammonia levels, which can lead to stress and disease in fish. Consequently, this program aims to implement Internet of Things (IoT) technology based on a Recirculating Aquaculture System (RAS) as an innovative solution for real-time monitoring of pond water quality. The methods employed include technical assistance and training for the community partner, the Bintang Rosela Jaya group, through the installation of an IoT system that monitors temperature, pH, ammonia, and total dissolved solid (TDS) parameters. Program evaluation is conducted using pre-tests and post-tests to assess the improvement in participants' knowledge and skills. Evaluation results indicate a significant increase in the average scores of participants' understanding from 60 (pre-test) to 73 (post-test). Furthermore, the application of IoT technology has proven to enhance farming efficiency by reducing disease risks and facilitating water quality management. In conclusion, this program has successfully bolstered the capacity of partners in the adoption of innovative technologies in aquaculture, thereby supporting the sustainability of catfish farming operations and enhancing competitiveness in the national fisheries market.